Five-Factor Authentication System with a Track and Trace Capability for Online Banking Platforms - Moepi, Glen; Mathonsi, Topside E. (The Indonesian Journal of Computer Science, 2025)
Online banking is a rapidly growing customer service platform, but increasing cyber threats require constant security improvements. This study developed an enhanced Multi-Factor Authentication (MFA) scheme with track-and-trace capabilities to mitigate risks. The proposed system includes five authentication modalities: username, password, PIN, OTP, biometrics (fingerprint or facial scan), registered smart devices, and a time-locked user location. A major feature is its ability to detect suspicious activities and send alerts via secretly obtained photos and location triangulation. Using design science methodology, three prototype schemes were developed and compared with First National Bank (FNB) and Standard Bank (STD) security systems. Evaluated with Datadog and AppDynamics APM tools, the best prototype achieved 80% security, slightly below FNB and STD’s 90%. It matched them in resource efficiency and outperformed them in response time, averaging 500 milliseconds compared to FNB’s 700 ms and STD’s 1000 ms.